Resolving Individual Labor Disputes in UAE Law: Critical Analytical Study - Nada Muhammad Al-Mazmi (Journal of Legal Sciences, 2024)
The study deals with the issue of resolving individual labor disputes in the UAE law, according to which the jurisdiction to settle individual labor disputes was distributed between the Ministry of human resources and Emiratisation and the judiciary, and the problem of the study revolved around the need to remove the ambiguity of some of the rules contained in the text of the article, and the need to amend some of them either to remove a conflict, or to achieve some important general principles. The study aims to clarify the cases and conditions of the jurisdiction of the Ministry of human resources and Emiratisation and the competent court to adjudicate individual labor disputes. And to find out the implications of their respective competence. To achieve these goals, the descriptive-analytical method and the critical method were used. The study of the subject came in two papers, the first one on the competence of the Ministry of human resources and Emiratisation to adjudicate individual labor disputes, and the competence of the court of First Instance to adjudicate individual labor disputes in the second one. At the end of the study, some of the most important results were reached: the UAE legislator identified the cases of the competence of the Ministry of human resources and Emiratisation to adjudicate individual labor disputes and made their adjudication within friendly solutions, and determined the jurisdiction of the court of First Instance of the same type of cases and made their adjudication within judicial solutions. The most important recommendations were: the need to impose judicial control over the decisions issued by the Ministry of human resources and Emiratisation on amicable settlements in individual labor disputes, especially with the granting of the status of the executive authority for those decisions, similar to what the family mentor issues on disputes of personal status issues.